2017
DOI: 10.18632/oncotarget.15844
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microRNA 885-5p as a novel regulator of tumor metastasis by targeting CPEB2 in colorectal cancer

Abstract: Colorectal cancer is the third most common cancer in the world and liver is the most frequent site of distant metastasis with poor prognosis. The aim of this study is to investigate microRNAs leading to liver metastasis. We applied microarray analysis and quantitative PCR to identify and validate dysregulated miRNAs in liver metastases when compared to primary CRCs. Functional significance and the underlying molecular mechanism of selected miRNA was demonstrated by a series of in vitro and in vivo assays. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…Furthermore, miR-885-5p has been reported to target cyclin-dependent kinase 2 and minichromosome maintenance complex component 5, activate cellular tumor antigen p53, and inhibit neuroblastoma proliferation and survival (24). Although previous work indicated that miR-885-5p was significantly upregulated in liver metastasis and colorectal cancer, and activated epithelial-to-mesenchymal transition (25), it was hypothesized that miR-885-5p may interact with alternative proteins and serve different functions in liver metastasis and colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, miR-885-5p has been reported to target cyclin-dependent kinase 2 and minichromosome maintenance complex component 5, activate cellular tumor antigen p53, and inhibit neuroblastoma proliferation and survival (24). Although previous work indicated that miR-885-5p was significantly upregulated in liver metastasis and colorectal cancer, and activated epithelial-to-mesenchymal transition (25), it was hypothesized that miR-885-5p may interact with alternative proteins and serve different functions in liver metastasis and colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 Moreover, miRNAs are validated to be intricately involved in the regulation of tumor metastasis and epithelial-mesenchymal transition. 11 , 12 , 13 , 14 , 15 , 16 MicroRNA-106a-5p (MiR-106a-5p), a member of the miR-17 family, has been reported to be aberrantly regulated in a diversity of tumors. It is considerably downregulated and proved to exert tumor suppressor effects in astrocytoma, osteosarcoma and colorectal cancer.…”
mentioning
confidence: 99%
“…Upregulation of this microRNA has been linked to enhanced proliferation and migration [33], and the development of liver and lung metastases in colorectal cancer. [34] In contrast, miR-885-5p suppressed proliferation, migration and invasion in vitro in osteosarcoma cells, and was downregulated in osteosarcoma patients with low expression levels being associated with a poor prognosis. [35] In our study, miR-885-5p was downregulated in the recurrent tumors, possibly matching the findings in osteosarcoma with low levels of miR-885-5p being associated with more proliferation and a poorer prognosis.…”
Section: Discussionmentioning
confidence: 94%